Pengaruh program keagamaan dan sokongan sosial terhadap konsep kendiri, kebimbangan dan kemurungan: Kajian dalam kalangan banduan wanita di Malaysia / Siti Jamiaah Abdul Jalil - Siti Jamiaah , Abdul Jalil (2017)
This study aims to identify the influence of religious programs and social support on the self-concept, anxiety and depression among female inmates. Among the aspects that have been examined are related to religious programs conducted in prisons known as the Program Pembangunan Sahsiah (PPS) or the Personality Development Program as well other forms of social support provided by the Malaysian Prison Department (JPM) to its prisoners. This study applies the quantitative and qualitative methods. The quantitative method uses questionnaires distributed among 141 respondents, convicted inmates who were all Malaysians and Muslims. Questionnaires were used to evaluate the respondents’ religious values, social support, self-concept, level of anxiety and depression of respondents. Descriptive analysis, ANOVA, T-test, correlation and regression were used to obtain research data. The qualitative data were obtained from interviews with four respondents. The descriptive analysis found that there is a min decrease from the group of respondents who are undergoing PPS to the respondents who have passed PPS. While the correlation analysis found that, basic religious values from the theological strength aspect have been able to provide positive impact on the self-concept and curb the problem of anxiety and depression of the inmates. The social supports received by the inmates are deemed to provide positive effects on their self-concept and depression, and not on their anxiety. Based on the regression analysis, the study shows that religious and social support programs have influenced the development of positive self-concept and problem of depression among the female inmates, but have no influence on their anxiety. The research implications suggest that PPS that was under Pelan Pembangunan Insan (PPI), or Human Development Program requires further improvement.